Ranking of Bioresources for Biogas Production - Bumbiere Ketija; Gancone Agita; Pubule Jelena; Kirsanovs Vladimirs; Vasarevicius Saulius; Blumberga Dagnija (Environmental and Climate Technologies, 2020)
Production of biogas using bioresources of agricultural origin plays an important role in Europe’s energy transition to sustainability and to a climate-neutral economy. The usage of some substrates like maize has been increasingly denounced in the last years and there is currently an active discussion about future subsidies to biogas producers depending on the substrate used. The aim of this study is to compare and rank different substrates for biogas production considering their economic feasibility, substrate efficiency and environmental aspects. During the research, eight substrates were evaluated: cattle manure, pig manure, poultry manure, straw, wood, maize silage, waste, and sewage sludge. In order to reach the research goal, multi-criteria analysis using TOPSIS methodology was applied to objectively determine which of the substrates considered would be the most suitable for biogas production in Latvia. The results obtained showed that pig manure is the most suitable raw material for biogas production in Latvia, while poultry manure was ranked second, with little difference in value from pig manure.